2013
DOI: 10.1371/journal.pone.0055526
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in ROS Activity and Lysosomal pH Account for Distinct Patterns of Macroautophagy in LINCL and JNCL Fibroblasts

Abstract: Neuronal Ceroid Lipofuscinoses (NCL) are lysosomal storage disorders characterized by the accumulation of lipofuscin within lysosomes. Late infantile (LINCL) and juvenile (JNCL) are their most common forms and are caused by loss-of-function mutations in tripeptidyl peptidase 1 (TPP1), a lysosomal endopeptidase, and CLN3 protein (CLN3p), whose location and function is still controversial. LINCL patients suffer more severely from NCL consequences than JNCL patients, in spite of having in common an abnormal accum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
80
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 45 publications
4
80
0
Order By: Relevance
“…This was consistent with SCMAS being released from lysosomes through LMP, suggesting that LMP is a previously unrecognized pathogenic event in CLN2 disease linking LMP and the autophagic machinery ( 67 ). This is supported by studies in human fi broblasts from patients with CLN2 disease showing increased levels of ROS, a well-described inducer of LMP ( 135 ).…”
Section: Calcium Homeostasismentioning
confidence: 65%
“…This was consistent with SCMAS being released from lysosomes through LMP, suggesting that LMP is a previously unrecognized pathogenic event in CLN2 disease linking LMP and the autophagic machinery ( 67 ). This is supported by studies in human fi broblasts from patients with CLN2 disease showing increased levels of ROS, a well-described inducer of LMP ( 135 ).…”
Section: Calcium Homeostasismentioning
confidence: 65%
“…Impaired fluid phase endocytosis has been reported for Cln3 mutant yeast, Cln3 −/− mouse brain endothelial cells, Cln3 −/− neuronal cells, and in fibroblasts harvested from patients with CLN3 deficiency (Codlin et al, 2008; Fossale et al, 2004; Luiro et al, 2004; Schultz et al, 2014; Vidal-Donet et al, 2013). We therefore measured fluid-phase endocytosis by uptake of fluorescently labeled dextran in cells treated with CBX or vehicle.…”
Section: Resultsmentioning
confidence: 96%
“…Work in model systems over the last two decades suggest that CLN3 impacts multiple cellular functions including lysosomal pH (Golabek et al, 2000; Holopainen et al, 2001; Pearce et al, 1999; Pearce and Sherman, 1998), vesicular trafficking (Cao et al, 2006; Codlin and Mole, 2009; Fossale et al, 2004; Kama et al, 2011; Metcalf et al, 2008), palmitoyl desaturase activity (Narayan et al, 2006), endocytosis (Codlin et al, 2008; Fossale et al, 2004; Luiro et al, 2001; Luiro et al, 2004; Schultz et al, 2014; Tecedor et al, 2013; Vidal-Donet et al, 2013), and membrane microdomain formation or stability (Tecedor et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…Although the established autophagy-related phenotypes in CLN3 models and the relationship of these to neurodegeneration in JNCL are incompletely understood, we further reasoned that developing a screening assay around autophagy in an accurate genetic model would serve as a useful starting point because abnormalities in autophagy are detected early in the disease process (17). Furthermore, the CLN3 protein is documented to be present in autophagosomes and autolysosomes/lysosomes (17), and defects in this pathway are hypothesized to be important in the development of mitochondrial ATPase subunit c-containing lysosomal storage material, a pathological hallmark in JNCL and other forms of NCL (17,42,50). Here, we have successfully developed a GFP-LC3-based autophagy assay in our murine cerebellar neuronal progenitor cell model of JNCL, and importantly, we have demonstrated that chemical biology studies using this model can successfully identify compounds with conserved bioactivity in human JNCL patient-derived disease relevant cell types.…”
Section: Discussionmentioning
confidence: 99%